Wnt signaling dynamics in head and neck squamous cell cancer tumor‐stroma interactions. Issue 3 (28th November 2018) - Le, Phuong N.; Keysar, Stephen B.; Miller, Bettina; Eagles, Justin R.; Chimed, Tugs‐Saikhan; Reisinger, Julie; Gomez, Karina E.; Nieto, Cera; Jackson, Brian C.; Somerset, Hilary L.; Morton, John J.; Wang, Xiao‐Jing; et al.
Abstract : Wnt pathway activation maintains the cancer stem cell (CSC) phenotype and promotes tumor progression, making it an attractive target for anti‐cancer therapy. Wnt signaling at the tumor and tumor microenvironment (TME) front have not been investigated in depth in head and neck squamous cell carcinoma (HNSCC). In a cohort of 48 HNSCCs, increased Wnt signaling, including Wnt genes ( AXIN2, LGR6, WISP1 ) and stem cell factors ( RET, SOX5, KIT ), were associated with a more advanced clinical stage. Key Wnt pathway proteins were most abundant at the cancer epithelial‐stromal boundary. To investigate these observations, we generated three pairs of cancer‐cancer associated fibroblast (CAF) cell lines derived from the same HNSCC patients. 3D co‐culture of cancer spheres and CAFs mimicked these in vivo interactions, and using these we observed increased expression of Wnt genes (eg, WNT3A, WNT7A, WNT16 ) in both compartments. Of these Wnt ligands, we found Wnt3a, and less consistently Wnt16, activated Wnt signaling in both cancer cells and CAFs. Wnt activation increased CSC characteristics like sphere formation and invasiveness, which was further regulated by the presence of CAFs. Time lapse microscopy also revealed preferential Wnt activation of cancer cells. Wnt inhibitors, OMP‐18R5 and OMP‐54F28, significantly reduced growth of HNSCC patient‐derived xenografts and suppressed Wnt activation at the tumor epithelial‐stromal boundary. Taken together, our findings suggest that Wnt signaling is initiated in cancer cells which then activate CAFs, and in turn perpetuate a paracrine signaling loop. This suggests that targeting Wnt signaling in the TME is essential.